IMPOLITENESS IN INDONESIAN TELEVISON SERIES: A CASE STUDY OF VERBAL ABUSE IN ANAK LANGIT TV SERIES - Ida Ayu Savitri; Riris Tiani (Sabda: Jurnal Kajian Kebudayaan, 2017)
Anak Langit is an Indonesian sinema elektronik (sinetron) or electronic cinema, a kind of tv series, for teenagers since most of the main characters are teenagers. Young viewers love this tv series as it tells us about the life of a motor gang in a big city which becoming a trend recently in several big cities in Indonesia. Although the main characters show the viewers how to be a good motor gang with positive attitude, we consider the language of this TV series is impolite as the rival of this motor gang often shows verbal abuse in most of their scenes using Bahasa Indonesia dialect  Betawi (the language of Betawi people, the people of Betawi Kampong in Jakarta). Those impolite utterances may be used to show the real life, including the colloquial language, of Jakarta/Betawi people which sometimes considered impolite by common people. It may be also done to strengthen the characteristics of the antagonist ones who are impolite and rude. In Pragmatics Study, impoliteness violates the Maxims of Politeness Principles. This violation can be seen as electronic media violence that may influence viewers to imitate the verbal abuse such as using the impolite utterance or doing the violence. In the end, it may leads into violence and less pro-social behaviour